2019
DOI: 10.31234/osf.io/ypj9v
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How strongly do moral character inferences predict forecasts of the future? Testing the moderating roles of transgressor age, implicit personality theories, and belief in karma

Abstract: Three studies (total N = 1486) investigated how inferences about a person’s current moral character guide forecasts about that person’s future moral character and future misfortunes, and tested several plausible moderating variables. Inferences about current moral character related (very strongly) to forecasts about future moral character and also (less strongly) to forecasts about future misfortunes. These relationships were moderated by two variables: Relations between inferences and forecasts were somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Results from Studies 1 to 4 showed that, compared with other fundamental motives, a person’s kin care motives were perceived to be especially stable. This finding is perhaps especially intriguing when considered alongside prior evidence suggesting that moral character is also perceived to persist (Goodwin et al, 2014; White et al, 2020). Additional results from Study 5 revealed that both kin care and mate retention motives were perceived to be highly diagnostic of traits connoting behavioral inclinations toward competence, dependability, warmth, and trustworthiness.…”
Section: Discussionmentioning
confidence: 73%
“…Results from Studies 1 to 4 showed that, compared with other fundamental motives, a person’s kin care motives were perceived to be especially stable. This finding is perhaps especially intriguing when considered alongside prior evidence suggesting that moral character is also perceived to persist (Goodwin et al, 2014; White et al, 2020). Additional results from Study 5 revealed that both kin care and mate retention motives were perceived to be highly diagnostic of traits connoting behavioral inclinations toward competence, dependability, warmth, and trustworthiness.…”
Section: Discussionmentioning
confidence: 73%